A note on the rational homological dimension of lattices in positive characteristic - Hughes, S (Cambridge University Press, 2022)
We show via ℓ2 -homology that the rational homological dimension of a lattice in a product of simple simply connected Chevalley groups over global function fields is equal to the rational cohomological dimension and to the dimension of the associated Bruhat–Tits building.